Targeted transcriptomic analyses of RNA isolated from formalin‐fixed and paraffin‐embedded human menisci. Issue 5 (18th August 2021) - Monibi, Farrah A.; Pannellini, Tania; Croen, Brett; Otero, Miguel; Warren, Russell; Rodeo, Scott A.
Abstract: Formalin‐fixed and paraffin‐embedded (FFPE) biospecimens are a valuable and widely‐available resource for diagnostic and research applications. With biobanks of tissue samples available in many institutions, FFPE tissues could prove to be a valuable resource for translational orthopaedic research. The purpose of this study was to characterize the molecular profiles and degree of histologic degeneration on archival fragments of FFPE human menisci obtained during arthroscopic partial meniscectomy. We used FFPE menisci for multiplexed gene expression analysis using the NanoString nCounter® platform, and for histological assessment using a quantitative scoring system. In total, 17 archival specimens were utilized for integrated histologic and molecular analyses. The median patient age was 22 years (range: 14–62). We found that the genes with the highest normalized counts were those typically expressed in meniscal fibrocartilage. Gene expression differences were identified in patient cohorts based on age (≤40 years), including genes associated with the extracellular matrix and tissue repair. The majority of samples showed mild to moderate histologic degeneration. Based on these data, we conclude that FFPE human menisci can be effectively utilized for molecular evaluation following a storage time as long as 11 years. Statement of Clinical Significance: The integration of histological and transcriptomic analyses described in this study will be useful for future studies investigating the basis for biological classification of meniscus specimens in patients. Further exploration into the genes and pathways uncovered by this study may suggest targets for biomarker discovery and identify patients at greater risk for osteoarthritis once the meniscus is torn.